A Hak Guna Usaha di Ibu Kota Nusantara: Analisis Implikasi Hukum Agraria terhadap Fungsi Sosial Tanah dan Keberlanjutan - Saim Aksinuddin; Subelo Wiyono (Faculty of Law, Universitas Pekalongan, 2025)
The granting of Cultivation Rights (HGU) in the Nusantara Capital City (IKN) serves as a crucial instrument to support long-term investment aimed at achieving inclusive and sustainable national development. However, the extended duration of HGU, reaching nearly two centuries, poses significant challenges, particularly in ensuring the alignment of this policy with the principles of national agrarian law as stipulated in Law No. 5 of 1960 on Basic Agrarian Regulations (UUPA). Article 6 of the UUPA emphasizes that all land rights carry a social function, requiring the use of land to benefit the broader community. This study analyzes the agrarian law implications of granting HGU in IKN concerning social justice, environmental sustainability, and the protection of indigenous community rights. Using a normative juridical approach, the research examines Law No. 3 of 2022 on IKN, Government Regulation No. 12 of 2023, and the principles of national agrarian law. The findings indicate that while the HGU policy provides certainty for investors, it has the potential to create social disparities, disregard the rights of indigenous communities over customary land, and trigger the exploitation of natural resources, leading to ecosystem degradation. As a solution, the study recommends periodic evaluation mechanisms, protection of indigenous community rights through public consultations and fair compensation, as well as harmonization of agrarian regulations. The implementation of digital technology is also essential to enhance transparency and public participation. With inclusive, sustainable policies grounded in the social function of land, IKN can become a symbol of equitable and environmentally friendly national development transformation.